Proceedings of the 7th Annual International Seminar on Transformative Education and Educational Leadership, AISTEEL 2022, 20 Se 2022
DOI: 10.4108/eai.20-9-2022.2324807
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of STAD Type Cooperative Learning Model with TGT Type and Achievement Motivation on Economic Learning Outcomes

Abstract: The purpose of this study is to produce economic learning using the STAD learning model and the TGT type learning model. It is known that students' economic learning outcomes have high and low achievement motivation, and know their learning outcomes. the interaction between these models can influence economic learning outcomes. This research method uses factorial 2 x 2 ANOVA. The results show that learning outcomes with the STAD learning model are higher than TGT. Learning outcomes with high achievement motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…The most prevalent topic that emerged from comments was acknowledgment, while other themes like inspiration and autonomy also appeared. The study found that the best methods for encouraging workers to produce their best work are praise, criticism, and rewards [14].…”
Section: Relationship Between Motivational Factors and Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent topic that emerged from comments was acknowledgment, while other themes like inspiration and autonomy also appeared. The study found that the best methods for encouraging workers to produce their best work are praise, criticism, and rewards [14].…”
Section: Relationship Between Motivational Factors and Job Satisfactionmentioning
confidence: 99%
“…An optimistic outlook and constructive habits help people accomplish more [15]. Moreover, based on research conducted by Butar-Butar [14] regarding the effect of achievement motivation and work procedures on performance mediated by affective commitment, it is concluded that achievement motivation has a positive and insignificant effect on employee performance. Employees who are well rewarded believe that the firm values them.…”
Section: Relationship Between Motivational Factors and Job Satisfactionmentioning
confidence: 99%